The Child and the State in India : Child Labor and Education Policy in Comparative Perspective - Weiner, Myron (Calcutta Oxford University Press, 1991)
India has the largest number of non-schoolgoing working children in the world. Why has the government not removed them from the labor force and required that they attend school? To answer this question, this comparative study looks at why and when other states have intervened to protect children against parents and employers.
Include Index
Keywords: India -- Child labor -- Education, Compulsory